Teaching with technologies in nursing and the health professions strategies for engagement, quality, and safety - Bonnel, Wanda E.; Smith, Katharine Vogel; Hober, Christine L. (Springer Publishing Company, LLC, 2019)
"Written for new and aspiring nursing faculty, this unique book delivers broad teaching principles alongside strategies for selecting the best technology. New generations of students are increasingly familiar with technology, and require educators who can add to their skills and shape them with a specific health care focus. Faculty have a responsibility to help their students prepare for the workforce, one that increasingly relies on high technology to operate. The teaching principles discussed in this text illuminate the changing technologies used in education and practice, and provide strategies for selecting the best technology to obtain a specific learning objectives, assignments, and outcomes. Teaching with Technologies in Nursing and the Health Professions, Second Edition has been substantially revised to reflect changes within our health care system and includes two completely new chapters. Founded upon the Integrated Learning Triangle for Teaching with Technologies, a central organizing tool for lesson planning and decision-making, concepts throughout the text link to key quality and safety issues, population and public health exigencies, and systems approaches to care. Each chapter contains case examples, self-assessment tools, quick teaching tips, evidence-based review abstracts, Q&As answered by noted practice experts, and online resources for further learning."--Back cover.